2020
DOI: 10.3390/pathogens9121021
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance and Biofilm-Forming Ability in Enterococcal Isolates from Red Meat and Poultry Preparations

Abstract: This study investigated the resistance to antibiotics and the capacity to form a biofilm of 200 isolates of enterococci isolated from raw preparations of beef (51 strains), pork (47), chicken (50), and turkey (52) acquired in north-western Spain. Fifteen antimicrobials of clinical importance were tested by the disc diffusion method. The average number of resistances per strain was 4.48 ± 1.59. If resistant strains were taken together with those showing reduced susceptibility, the total number of resistances pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
4
12
0
1
Order By: Relevance
“…Previous studies showed that biofilm production is common in Enterococcus isolates from different origin (Baldassarri et al, 2001; Castaño‐Arriba et al, 2020; Goudarzi et al, 2018; Igbinosa & Beshiru, 2019), as confirmed in this study. Baldassarri et al (2001) reported strong biofilm production in 43% of their E. hirae , E. durans , E. casseliflavus , E. gallinarum , E. raffinosus , and E. avium isolates.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies showed that biofilm production is common in Enterococcus isolates from different origin (Baldassarri et al, 2001; Castaño‐Arriba et al, 2020; Goudarzi et al, 2018; Igbinosa & Beshiru, 2019), as confirmed in this study. Baldassarri et al (2001) reported strong biofilm production in 43% of their E. hirae , E. durans , E. casseliflavus , E. gallinarum , E. raffinosus , and E. avium isolates.…”
Section: Resultssupporting
confidence: 89%
“…Igbinosa and Beshiru (2019) indicated that 12, 19, and 37% of Enterococcus species from shrimps were strong, weak and moderate biofilm producers, repectively. Castaño‐Arriba et al (2020) found that 51, 78 and 71 of 200 enterococci from red meat and poultry preparations were weak, moderate and strong biofilm producers, respectively. In contrast to our data, some researchers found no biofilm formation in their E. casseliflavus and E. gallinarum isolates (Chajęcka‐Wierzchowska et al, 2016; Dworniczek et al, 2003; Gomes et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…MDR was frequently detected among the isolated enterococci in this study. The emergence of MDR enterococci has also been reported worldwide, particularly in Korea (26.9%), Spain (87.5%), and Ethiopia (78.2%), and is currently regarded as a growing public health concern [72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding E. durans and E. faecium isolates, resistance to penicillin, erythromycin, tetracycline, levofloxacin, norfloxacin, ciprofloxacin, chloramphenicol, and nitrofurantoin was reported (Table 2). Resistance to the latter three is of concern, for not being intrinsic in enterococci, and they are regarded as essential antibiotics for humankind [299,300]. Despite the presence of tetM, tetracycline resistance was not reported in E. faecium as per these studies.…”
Section: Enterococci As Reservoirs Of Antibiotic Resistancementioning
confidence: 98%